HUMAN CAPITAL DI ERA DIGITAL - Hani Damayanti Aprilia; Nur Efendi; A. Rifa'i (Jurnal Perspektif Bisnis, 2020)
The insurance industry shows rapid development which proven by the improvement of the number of users of insurance products and high level of competition. To be able to compete in the digital era, insurance companies must be supported by marketers who have the knowledge, expertise, abilities and skills that make human capital or company assets (human capital). Human capital development program is not just a cost, but a long-term investment that can benefit the company in the long term. This study was aimed to determine, describe, and analyze the development of human capital marketers in the digital era in terms of insurance industry (Prudential Indonesia). The data analysis used was an interactive data analysis model developed by Miles & Huberman. The results of the research showed that Prudential Indonesia developed the human capital as a strategy for Prudential Indonesia to be the best and undefeated insurance industry in the digital era through continuous and up-to-date training. The development of human capital for marketers is done through the identification of human capital components, so that the marketers have product knowledge, licenses, experience, appearance, networks / connections, self-quality, independent, and creative. The other components such as motivation, support leaders, organizational atmosphere, and work group effectiveness will also influence the marketers to be able to achieve higher performance in order to compete in the digital era. Program pengembangan human capital bukan hanya sekedar biaya, melainkan investasi jangka panjang yang dapat menguntungkan perusahaan dalam jangka waktu yang lama. Penelitian ini bertujuan untuk mengetahui, mendeskripsikan, dan menganalisis pengembangan human capital tenaga pemasar di era digital dalam industri asuransi (Prudential Indonesia). Analisis data menggunakan model interaktif yang dikembangkan oleh Miles & Huberman (2009). Hasil penelitian menunjukkan bahwa pengembangan human capital menjadi strategi untuk dapat bersaing di era digital melalui pelatihan yang berkelanjutan. Pengembangan dilakukan melalui identifikasi komponen human capital, agar tenaga pemasar memiliki pengetahuan produk, lisensi, pengalaman, penampilan, jaringan/koneksi, kualitas diri, mandiri, serta kreatif. Komponen lain seperti motivasi, support leader, suasana organisasi, dan efektifitas kelompok kerja juga akan mempengaruhi tenaga pemasar untuk dapat mencapai kinerja yang lebih tinggi agar dapat bersaing di era digital.